2010
DOI: 10.1172/jci42164
|View full text |Cite
|
Sign up to set email alerts
|

The endothelial cell receptor GRP78 is required for mucormycosis pathogenesis in diabetic mice

Abstract: Mucormycosis is a fungal infection of the sinuses, brain, or lungs that causes a mortality rate of at least 50% despite first-line therapy. Because angioinvasion is a hallmark of mucormycosis infections, we sought to define the endothelial cell receptor(s) for fungi of the order Mucorales (the fungi that cause mucormycosis). Furthermore, since patients with elevated available serum iron, including those with diabetic ketoacidosis (DKA), are uniquely susceptible to mucormycosis, we sought to define the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
323
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 279 publications
(333 citation statements)
references
References 43 publications
8
323
0
2
Order By: Relevance
“…Monocytes, macrophages, neutrophils as well as epithelial and endothelial cells [35], mostly contribute to the antifungal innate immune response through phagocytosis and direct pathogen killing. By contrast, uptake of fungi by DCs promotes the differentiation of naïve T cells into effector Th-cell subtypes (Fig.…”
Section: Immune Response To Fungi: Balance Between Tolerance and Pathmentioning
confidence: 99%
See 1 more Smart Citation
“…Monocytes, macrophages, neutrophils as well as epithelial and endothelial cells [35], mostly contribute to the antifungal innate immune response through phagocytosis and direct pathogen killing. By contrast, uptake of fungi by DCs promotes the differentiation of naïve T cells into effector Th-cell subtypes (Fig.…”
Section: Immune Response To Fungi: Balance Between Tolerance and Pathmentioning
confidence: 99%
“…Indeed, the immune system does not remain ignorant of commensal, passenger (transient), or opportunistic fungi, and sensing these different fungi through PRRs serve to ensure that both the symbiotic host-microbial relationship and a homeostatic balance between tolerogenic and proinflammatory immune responses are maintained. In light of this, tissue homeostasis and its possible breakdown in fungal infections and diseases play a fundamental role.A number of seminal reviews have addressed the importance of both resistance -the ability to limit microbial burden -and tolerance -the ability to limit the host damage caused by an uncontrolled response -as mechanisms of immune responses to fungi and the reader is directed to these for more in-depth information about specific immune mechanisms [31][32][33][34].Monocytes, macrophages, neutrophils as well as epithelial and endothelial cells [35], mostly contribute to the antifungal innate immune response through phagocytosis and direct pathogen killing. By contrast, uptake of fungi by DCs promotes the differentiation of naïve T cells into effector Th-cell subtypes (Fig.…”
mentioning
confidence: 99%
“…We have shown that Mucorales adhere to and invade endothelial cells (3) by expressing CotH proteins (4). CotH proteins bind to the heat shock host receptor glucose-regulated protein 78 (GRP78) (5), causing host cells to endocytose the organisms. We also found that elevated concentrations of glucose and iron, comparable to those seen during hyperglycemia and DKA, enhance GRP78 expression, leading to enhanced fungal invasion and damage of endothelial cells (5).…”
Section: Introductionmentioning
confidence: 99%
“…CotH proteins bind to the heat shock host receptor glucose-regulated protein 78 (GRP78) (5), causing host cells to endocytose the organisms. We also found that elevated concentrations of glucose and iron, comparable to those seen during hyperglycemia and DKA, enhance GRP78 expression, leading to enhanced fungal invasion and damage of endothelial cells (5). Consistent with in vitro data, mice with DKA were found to express more GRP78 in the target organs than normal mice and were protected from mucormycosis when given anti-GRP78 antibodies (5).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, diabetic patients with high serum iron level and glucose concentrations are more susceptible to mucormycosis than other high risk patients. Mucorales could invade the tissues by proteolytic, lipolytic, and glycosidic enzymes and also with metabolite products like mycotoxins such as agroclavine [6,8].…”
Section: Introductionmentioning
confidence: 99%